Perpetuating the cycle of violence in South African low-income communities: attraction to violence in young men exposed to continuous threat. Issue 1 (1st December 2016) - Hinsberger, Martina; Sommer, Jessica; Kaminer, Debra; Holtzhausen, Leon; Weierstall, Roland; Seedat, Soraya; Madikane, Solomon; Elbert, Thomas
Abstract : Background: Life in the low-income urban communities of South Africa is imprinted by a cycle of violence in which young males predominantly are in the roles of both victim and perpetrator. There is some evidence that adolescents who show an attraction to cruelty can display high levels of psychosocial functioning despite the presence of posttraumatic stress symptoms. However, the role of appetitive aggression in the context of ongoing threats and daily hassles is not yet fully understood. Objective: In this study, we examine the role of attraction to violence in areas of continuous traumatic stress exposure and its effect on posttraumatic stress disorder (PTSD) severity and violence perpetration. Method: A sample of 290 young males from two low-income Cape Town communities was surveyed. We assessed appetitive aggression with the Appetitive Aggression Scale (AAS), PTSD symptoms with the PTSD Symptom Scale-Interview, the number of witnessed and self-experienced traumatic event types with an adaptation of the Child Exposure to Community Violence questionnaire, and the number of perpetrated violence event types with an adapted offence checklist from the AAS. Results: Appetitive aggression scores were predicted by witnessed as well as self-experienced traumatic events. Higher appetitive aggression scores resulted in higher levels of PTSD severity and perpetrated violence. Conclusions: Young males living in the low-income areas of South Africa may develop an attraction to cruelty in response to exposure to violence. Their willingness to fight in turn can increase the likelihood of continued violent behaviour. In contrast to previous research from postconflict areas, appetitive aggression and engagement in violence do not prevent the development of PTSD, but are instead associated with higher levels of posttraumatic stress. PTSD symptoms such as avoidance and hyperarousal, as well as an attraction to cruelty and thus the willingness to fight, might support survival in areas of ongoing conflict, but at the same time they could fuel the cycle of violence.